Kinetic analysis for cyclic CO2 capture using lithium orthosilicate sorbents derived from different silicon precursors. Issue 27 (21st June 2018) - Zhao, Ming; Fan, Hanlu; Yan, Feng; Song, Yinqiang; He, Xu; Memon, Muhammad Zaki; Bhatia, Suresh K.; Ji, Guozhao
Abstract : The illustration of the CO2 sorption process in Li4 SiO4 . Abstract : A series of Li4 SiO4 was synthesized using LiNO3 and six different silicon precursors. The precipitated-silica-derived Li4 SiO4 presented the highest CO2 capacity in a 10 h sorption test, and ZSM-5-derived Li4 SiO4 demonstrated the most rapid CO2 sorption. The CO2 sorption kinetics predominantly followed the nucleation mode and could be accurately described by the Avrami-Erofeev model. The Avrami-Erofeev model provided an in-depth analysis of correlation between sorption performance and material properties. Both the nucleation speed and nucleation dimensionality affected the overall sorption kinetics. The kinetics and pore-size distribution suggest that the sorption kinetics was dependent on the quantity of ∼4 nm-pores which favors nucleation dimensionality. For the cyclic tests, the precipitated-silica-derived sample presented the poorest performance with the capacity decreasing from 31.33 wt% at the 1 st cycle to only 11.52 wt% at the 30 th cycle. However, the sample made from fumed silica displayed an opposite trend with the capacity increasing from 19.90 wt% at the 1 st cycle to 34.23 wt% at the 30 th cycle. The radically distinct behaviour of samples during cycles was on account of the alternation of sorption kinetics. The decrease in ∼4 nm-pores after cycles was responsible for the decrease of nucleation dimensionality for the precipitated-silica-derived sample. The rearrangement during cycles could enrich the pores of ∼4 nm for the fumed silica-derived sample, which improved the nucleation growth, thus enhancing the kinetics with cycles.